Strange parents, unrecognized child: The Genesis of Croatian Art History in the Vormärz Period - Špikić, Marko (Array, 2010)
As stated in Momigliano’s Ancient History and the Antiquarian, European antiquarian studies experienced the final transformation into modern disciplines of art history, archaeology and classical philology in the first half of the 19th century. In today’s Croatia, and especially in its southern region of Dalmatia for centuries existed a strong antiquarian tradition, founded by Ciriaco d’Ancona in the 15th century. Dalmatia attracted stronger attention of the European antiquarians with works by Spon and Wheler in 1678, Fischer von Erlach in 1721, Adam in 1764 and Fortis in 1774. These publications at the end of the 18th century encouraged the formation of a local antiquarian community. The aim of this paper is to discuss the importance of antiquarian tradition and its transformation under Austrian Emperors Francis I and Ferdinand I into art historical discipline. The author emphasizes the texts and some of the local and “national” protagonists that improved that process.